Hydrogen peroxide controls biofilm formation by Klebsiella pneumoniae e in vitro - Farah M. Saleh; Archana Saini (World Journal of Experimental Biosciences, 2019)
The biofilm formation of bacteria in medical devices especially indwelling urinary catheters considers one of the hospital complications of infections. Here, the anti-biofilm effect of hydrogen peroxide (H2O2) against biofilm produced by Klebsiella pneumoniae on urinary catheters was evaluated. In the present study, 2the five isolates of K. pneumoniae e e were isolated from urine samples of patients suffering from urinary tract infections (UTIs). The biochemical and VITIK technology was used to identify the bacterial isolates. The ability of K. pneumoniae to adhere and form biofilm onto the indwelling urinary catheter was measured. Moreover, the negative effect of different concentrations of H2O2 (0.01%, 0.02%, 0.04%, 0.08%, and 0.16%) on the biofilm formation of K. pneumoniae on the pieces of the indwelling urinary catheter was evaluated in test tubes (in vitro). The result showed that all isolates produced a high level of biofilm. Three isolates were considered moderated biofilm producers and 2 were considered strong biofilm producers. All the used concentrations of H2O2 were effect-negative (P
Keywords: Biofilm, H2O2, indwelling urinary catheter, Klebsiella pneumoniae.